Religion and identity in modern Russia: the revival of orthodoxy and Islam - Johnson, Juliet Ellen (Post-Soviet politics, 2005)
Religion after communism : belief, identity, and the Soviet legacy in Russia / Juliet Johnson -- Ethno-religious identity in modern Russia -- Orthodoxy and Islam compared / Marietta Stepaniants -- Orthodoxy, ethnicity, and mass ethnophobias in the late tsarist era / Liudmila Gatagova -- In search of the "Russian idea" : a view from inside the Russian Orthodox Church / Georgii Chistiakov -- Tolerance and extremism : Russian ethnicity in the Orthodox discourse of the 1990s / Svetlana Ryzhova -- Islam and the emergence of Tatar national identity / Aidar Yuzeev -- Islam and the construction of Tatar sociolinguistic identity / Suzanne Wertheim -- The search for ethnic and religious identity in Dagestan / Zagir Arukhov -- Modern identities in Russia : a new struggle for the soul? / Juliet Johnson